African agriculture and development - Brzeska, Joanna; Diao, Xinshen; Fan, Shenggen; Thurlow, James (International Food Policy Research Institute, 2012)
After decades of income divergence between Africa and the rest of the world, a new era appears to have begun in many African countries. The decade since 2000 has been one of macroeconomic stability, sustained economic growth, and improved governance. Although this performance was disrupted by the global recession and food crises in 2008–10, Africa was one of the less affected of the world’s developing regions. In fact, not only did growth accelerate in Africa during the 2000s, but this was also the first decade since the 1970s when Africa was not the slowest growing developing region (World Bank 2010a).2 It therefore marks a historic break from decades of internal and external deficits, economic stagnation, and political turmoil. Moreover, a wide range of African countries performed well, including oil-exporting and resource-rich countries, large and middle-income countries, and coastal and low-income countries (Arbache et al. 2008). The new millennium has heralded Africa’s first “decade of growth.”